If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4 + x) * 2 = 0 Reorder the terms for easier multiplication: 2(4 + x) = 0 (4 * 2 + x * 2) = 0 (8 + 2x) = 0 Solving 8 + 2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 2x = 0 + -8 2x = 0 + -8 Combine like terms: 0 + -8 = -8 2x = -8 Divide each side by '2'. x = -4 Simplifying x = -4
| 0.1(x-16)=0.6(x-1) | | 4a^2+7a-3=0 | | 19x-5=7+15x | | -(2-7x)= | | W+w+12=40 | | 2x^2-9x+9= | | 1/9(n+4/5)=-4/5(n+3/4) | | 2+3y=-1 | | 6a+(a+4)=(6a+a)+4 | | -3(x+9)=-45 | | m+5m+11=47 | | -2y+10=-3(2y+2) | | (7x+4)(2x^2-17x-9)= | | 0=-1.5a+3 | | -(7x-2)= | | -2(7w+6)=-14w+4 | | x+(x+25)+(3x)=435 | | -2(2+x)=-2x+1 | | -6x^2+15x=-7x-21 | | 48+8x=10x-6 | | n(n-1)(n-2)=0 | | 2x^2-7x+111=0 | | 3x^2-8x-11= | | -14a+6=12a-20 | | 5g-2g=45-2g | | A(b-6)= | | 4x^3+28x^2-120x=0 | | 3(x-2)+6=38.85 | | 5y-5=-2y+2 | | -2(3x-4)+12=28 | | 1.9+9.3=n+54.7 | | 0.45= |